From Guidelines to Action: Tackling Risk Factors for Surgical Site Infections - Caterina Elisabetta Rizzo; Roberto Venuto; Paola Tripodi; Linda Bartucciotto; Elvira Ventura Spagnolo; Antonio Nirta; Giovanni Genovese; Isabella La Spina; Sabrina Sortino; Alessandro Nicita; Francesco Loddo; Bruno Romeo; et al. (Antibiotics)
Background/Objectives: Surgical site infections are a serious public health concern, representing a significant burden on healthcare systems and society. Their occurrence is influenced by several factors, including patient demographics, healthcare facilities and the specific circumstances surrounding surgery. The use of prophylactic antibiotics in this context carries both potential benefits and risks. The aim of this study is to investigate potential risk factors that may adversely affect the development of SSIs, as well as to assess the appropriateness and adherence to perioperative antibiotic prophylaxis. Methods: This observational study was conducted from October 2023 to October 2024 at the University Hospital of Messina, Italy, a hospital performing both thoracic and vascular surgery. Data were collected using a questionnaire regarding socio-demographic data, risk factors, clinical and surgical data and details regarding the administration of antibiotics. Results: This study included 117 patients with an average age of 63 ± 12.36 SD years, 70.9% from the Thoracic Surgery Unit and 29.1% from the Vascular Surgery Unit. The most administered antibiotic was cefazolin, and antibiotic administration time was in compliance with the guidelines. Conclusions: Our data show that the implementation of evidence-based guidelines, healthcare professionals’ education and correct antibiotic use can reduce the burden of SSIs by improving patient care.